Can you find the golden ratio in your plate? - Deroy, O; Spence, C (BioMed Central, 2014)
A scientific approach to plating needs to be based on perceivers’ responses and anticipate possible cultural and individual differences. It cannot just follow common sense principles, whose validity remain untested and only attract journalists’ attention, like the claim that people will prefer food composition based on the golden ratio.